Assessing Readiness Index toward Industry 4.0 of SMEs Leather Industry in Yogyakarta's - Ratna Purwaningsih; Ade Aisyah Arifna Putri; Melati Syahrani Ryandy; Ary Arvianto; Chaterine Alvina Prima Hapsari; Rifki Daris Dzulfikar (Universitas Mercu Buana, 2026)
Objective: This study focuses on create a readiness index measurement model tailored to the transformation of technology in the creative industry for small and medium-sized enterprises (SMEs)measuring the readiness level of leather SMEs as they transition towards Industry 4.0. The indicators developed in INDI 4.0 need to be adjusted again when used to measure the readiness of the creative industry. After developing the measurement model, then proceed with test the model by using it to assess the readiness levels of leather SMEs in Yogyakarta. Based on the results of the readiness index assessment, which indicators need to be improved will be identified and be the basis for formulate recommendations to enhance the readiness levels of leather SMEs.Methodology: The research methodology is divided into Developing Measurement Indicators and Measuring Readiness Index. Developing indicators was conducted through literature review and validated with expert opinion using the Delphi method. Measuring the readiness index was conducted using the multidimensional scaling method and validated using the Monte Carlo method.Finding: The contribution of this research is to develop dimensions and indicators suitable for the creative industry. These additional indicators shed light on digitalization issues in marketing and finance that were not yet fully addressed in INDI 4.0. There is also additional collaboration to strengthen supply chain channels and expand factory operations. The result of measuring the readiness index give a value of 1.92, categorized as Level 1 (initial readiness). The highest value of readiness index is in the product and service dimension and the lowest value is in the technology dimension. The assessment results revealed several points on what the leather creative industry needs to improve to raise the readiness index such as strengthening business management skills, particularly related to digital marketing and financial skills, technology investments, and intensive collaboration with product suppliers and distributors.